2017
DOI: 10.1097/qad.0000000000001287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of depression and anxiety on antiretroviral therapy adherence among newly diagnosed HIV-infected Chinese MSM

Abstract: Objective To explore the effect of depression and anxiety on adherence to antiretroviral therapy (ART) among men who have sex with men (MSM) with newly diagnosed HIV infections. Design We conducted a prospective study of Chinese MSM with newly diagnosed HIV infections. Methods The Hospital Anxiety and Depression Scale (HADS) was used to measure depression and anxiety at baseline, 6 and 12 months, separately. ART adherence was self-reported once every three months (“perfect” or no missing dose in the past t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
2
43
0
2
Order By: Relevance
“…Anxiety and especially depression have consistently been associated with poor antiretroviral treatment (ART) adherence (Safren et al, 2016;Smith Fawzi et al, 2016;Tao et al, 2016;Tatum & Houston, 2016), and are linked to poor virological control and lower CD4 T cell counts (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety and especially depression have consistently been associated with poor antiretroviral treatment (ART) adherence (Safren et al, 2016;Smith Fawzi et al, 2016;Tao et al, 2016;Tatum & Houston, 2016), and are linked to poor virological control and lower CD4 T cell counts (Amanor-Boadu et al, 2016;Herkenham & Kigar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological dysfunction, including anxiety and depression, can negatively influence treatment adherence, and can increase substance use in PLWH (Schadé, van Grootheest, & Smit, 2013; Tao et al, 2016). One study also found that those with higher self-reported trait anger, or general feelings of anger, had a decreased likelihood of adhering to a consistent antiretroviral therapy (ART) regimen.…”
mentioning
confidence: 99%
“…This developmental model argues that early stressors associated with sexual minority status produce external and internal stress processes (eg, antigay prejudice, discrimination, internalised homophobia, expectations of rejection) that contribute to mental health and recreational drugs use disorders later in life 26. Work in China has suggested that depression is associated with lower adherence to antiretroviral drugs and also to higher stigma related to male homosexuality27; it would be important to also study these dynamics with syphilis, as a curable STI.…”
Section: Discussionmentioning
confidence: 99%